The revenues obtained from the Fish Farming in the province of Wasit - Jidran, Kareem Khudhair (Iraqi Journal of Aquaculture, 2022)
This research was conducted in the province of Waist. The town of Hafria during (2009 - 2010) to determine the feasibility of fish farming in fish ponds. Which is the most common method in Iraq. The total number of fish farms in the whole of the province was 175 farms. The total area of these farms was 10011 Donam (1/4 hectare). While their water area was1667.5 Hectare. The capacity of these farms was 6670000 fingerlings. These farms lie mainly in the northern part of the province. i.e.. in Al- Azizia city and especially in the town of Al-Hafria which is adjacent to the southern border lines of Baghdad province. The total number of these farms is 47 which form 56.6 % from the total number of farms in this city of Al-Azizia, and 26.9 % from the total number of fish farms in the whole province. Their area is (2425) Donam and their water area is 1964 Donam while their Fish ponds were 278 the total capacity of those basins is 1964000 fingerlings. This study deals with the evaluation and analysis of the feasibility of these projects in this region. An arbitrary specimen of ten projects was taken which formed 33% from the working farms. The evaluation was done by using 21 economic standards. The value of these standards calculated on the basis of a single Donam which showed the success of each project. When evaluated in isolation. It also showed the feasibility of all the projects after calculating the costs and revenues. These fish farms also proved successful under the risky conditions when an increase of 10% in the costs and a stability in the costs. The results of the statistical analysis have also shown significant differences among these fish farms. The matter which would encourage projects owners to keep on investing in spite of the fluctuations in prices and in the quality and quantity of inputs and outputs. Resulting from the unstable conditions of the local markets.